The development of risk aversion and prudence in Chinese children and adolescents - Timo Heinrich; Jason Shachat (Journal of Risk and Uncertainty, 2021)
This study experimentally evaluates the risk preferences of children and adolescents living in an urban Chinese environment. We use a simple binary choice task that tests risk aversion, as well as prudence. This is the first test for prudence in children and adolescents. Our results reveal that subjects from grades 5 to 11 (10 to 17~years) make mostly risk-averse and prudent choices. The choices of 3rd graders (8 to 9~years) do not differ statistically from risk neutral benchmarks, but at the same time they make mostly prudent choices. We also find evidence for a transmission of risk preferences. There is positive correlation between all children's and their parents' tendency to make risk-averse choices. There is also positive correlation between girls' and their parents' tendency to make prudent choices.
Keywords: C93; D81; J13; 300; Risk aversion; Prudence; Transmission of preferences; Age effects; Experimental economics; Children